Some Population Set-Based Methods for Unconstrained Global Optimization - Kaelo, Professor (My University, 2006)
Many real-life problems are formulated as global optimization problems with continuous variables. These problems are in most cases nonsmooth, nonconvex and often simulation based, making gradient based methods impossible to be used to solve them. Therefore, efcient, reliable and derivative-free global optimization methods for solving such problems are needed. In this thesis, we focus on improving the efciency and reliability of some global optimization methods. In particular, we concentrate on improving some population set-based methods for unconstrained global optimization, mainly through hybridization. Hybridization has widely been recognized to be one of the most attractive areas of unconstrained global optimization. Experiments have shown that through hybridization, new methods that inherit the strength of the original elements but not their weakness can be formed. We suggest a number of new hybridized population set-based methods based on differential evolution (de), controlled random search (crs2) and real coded genetic algorithm (ga). We propose ve new versions of de. In the rst version, we introduce a localization, called random localization, in the mutation phase of de. In the second version, we propose a localization in the acceptance phase of de. In the third version, we form a de hybrid algorithm by probabilistically combining the point generation scheme of crs2 with that of de in the de algorithm. The fourth and fth versions are also de hybrids. These versions hybridize the mutation of de with the point generation rule of the electromagnetism-like (em) algorithm. We also propose ve new versions of crs2. The rst version modies the point generation scheme of crs2 by introducing a local mutation technique. In the second and third modications, we probabilistically combine the point generation scheme of crs2 with the linear interpolation scheme of a trust-region based method. The fourth version is a crs hybrid that probabilistically combines the quadratic interpolation scheme with the linear interpolation scheme in crs2. In the fth version, we form a crs2 hybrid algorithm by probabilistically combining the point generation scheme of crs2 with that of de in the crs2 algorithm. Finally, we propose ve new versions of the real coded genetic algorithm (ga) with arithmetic crossover. In the rst version of ga, we introduce a local technique. We propose, in the second version, an integrated crossover rule that generates two children at a time using two different crossover rules. We introduce a local technique in the second version to obtain the third version. The fourth and fth versions are based on the probabilistic adaptation of crossover rules. The efciency and reliability of the new methods are evaluated through numerical experiments using a large test suite of both simple and difcult problems from the literature. Results indicate that the new hybrids are much better than their original counterparts both in reliability and efciency. Therefore, the new hybrids proposed in this study offer an alternative to many currently available stochastic algorithms for solving global optimization problems in which the gradient information is not readily available.
Student Number : 0214677F - PhD thesis - School of Camputational and Applied Mathematics - Faculty of Science
Keywords: global optimization; genetic algorithms; operations research; direct search methods; differential evolution; controlled random search; probabilistic adaptation; non-linear optimization; heuristics; hybridization; programming model; derivative-free; optimization problem